(untitled) - Fogelin, Robert J. (Fort Worth, TX, 2001)
The proven strengths of this established text include the philosophy of language, analysis of arguments as they occur in ordinary language, and systematic examination of inductive arguments. The book covers statistical generalizations, statistical syllogisms, and inferences to the best explanation.
Keywords: Logic,Lôgic học